Methylation-mediated miR-155-FAM133A axis contributes to the attenuated invasion and migration of IDH mutant gliomas. (28th September 2018) - Huang, Guo-Hao; Du, Lei; Li, Ningning; Zhang, Ying; Xiang, Yan; Tang, Jun-Hai; Xia, Shuli; Zhang, Eric Erquan; Lv, Sheng-Qing
Abstract: Gliomas with isocitrate dehydrogenases gene mutations ( IDH MT ) were found to be less aggressive than their wildtype ( IDH WT ) counterparts. However, the mechanism remains unclear. The current study aims to investigate the role of silenced oncogenic microRNAs in IDH MT gliomas, which were largely ignored and may contribute to the less aggressive behavior of IDH MT gliomas. Microarrays, bioinformatics analysis of the data from TCGA and qPCR analysis of samples from our experimental cohort (LGG: IDH WT  = 10, IDH MT  = 31; GBM: IDH WT  = 34, IDH MT  = 9) were performed. The results show that miR-155 was consistently down-regulated in IDH MT gliomas. Establishment of IDH1 R132H overexpressing glioma cell line and bisulfite sequencing PCR suggested that miR-155 down-regulation was associated with IDH1 R132H mutation induced promoter CpG islands methylation. The cancer testis antigen FAM133A is a direct downstream target of miR-155 and is a negative regulator of glioma invasion and migration possibly by regulating matrix metallopeptidase 14 (MMP14). Together, we found that methylation-regulated miR-155-FAM133A axis may contribute to the attenuated invasion and migration of IDH MT gliomas by targeting MMP14. Highlights: MiR-155 is down-regulated in IDH MT gliomas and is an independent risk factor for glioma patients. MiR-155 is down-regulated via IDH mutation-induced promoter CpG island methylation. Cancer testis antigen FAM133A is a direct downstream target of miR-155. FAM133A predicts favorable prognosis for glioma patients. Down-regulation of FAM133A promotes glioma invasion/migration by regulating MMP14.